Glycine max Homologs of DOESN'T MAKE INFECTIONS 1, 2, and 3 Function to Impair Heterodera glycines Parasitism While Also Regulating Mitogen Activated Protein Kinase Expression - Khatri, Rishi; Pant, Shankar R.; Sharma, Keshav; Niraula, Prakash M.; Lawaju, Bisho R.; Lawrence, Kathy S.; Alkharouf, Nadim W.; Klink, Vincent P. (Frontiers in Plant Science, 2022)
Glycine max root cells developing into syncytia through the parasitic activities of the pathogenic nematode Heterodera glycines are isolated by laser microdissection (LM). Microarray analyses identify G. max DOESN’T MAKE INFECTIONS3 (DMI3) expression in syncytia undergoing parasitism, but during a defense response. DMI3 encodes part of the common symbiosis pathway (CSP) involving DMI1, DMI2, and other CSP genes. The identification of the expression of DMI genes in syncytia undergoing a defense response, and their role in symbiosis, suggests the possible existence of commonalities between symbiosis and defense. G. max has 3 DMI1, 12 DMI2, and 2 DMI3 paralogs. LM-assisted gene expression experiments of isolated syncytia under further examination here show G. max DMI1-3, DMI2-7, and DMI3-2 expression occurring during the defense response in the H. glycines-resistant genotypes G. max[Peking/PI 548402] and G. max[PI 88788]. Transgenic overexpression (OE) and RNA interference (RNAi) analyses for G. max DMI1-3, DMI2-7, and DMI3-2 reveal a defense function to H. glycines parasitism. Prior functional transgenic analyses of the 32-member G. max mitogen activated protein kinase (MAPK) gene family determine that 9 of them act in the defense response to H. glycines parasitism and are referred to as defense MAPKs. RNA-seq analyses of root RNA isolated from the 9 G. max defense MAPKs undergoing OE or RNAi reveal they alter the relative transcript abundances (RTAs) of specific DMI1, DMI2, and DMI3 paralogs. The RTA of DMI3-2, undergoing expression in syncytia during defense, is also increased by MAPK3-1-OE. In contrast, an examination of MAPK3-1 and MAPK3-2 expression show their RTAs sometimes are influenced by transgenically-manipulated DMI1-3, DMI2-7, and DMI3-2 expression. The results show G. max homologs of the CSP, and defense pathway are linked, apparently involving co-regulated gene expression.